The Effect of Work Motivation and Work Discipline on Employee Performance - Steven Julianto; Editya Nurdiana (Greenation Research & Yayasan Global Resarch National, 2026)
This study was conducted against the background of fluctuating employee performance and service quality challenges in the competitive culinary industry, specifically at Sate Taichan Kopi Nama Cirebon. The objective of this research was to examine and analyze the effect of work motivation and work discipline on employee performance, both partially and simultaneously. The research object consisted of employees working at Sate Taichan Kopi Nama Cirebon. This study employed a quantitative causal research method with a survey approach. The sample included 80 employees selected from a population of 100 using the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression with statistical software. The results of the study showed that work motivation has a positive and significant effect on employee performance, indicating that psychological encouragement and recognition play an important role in improving work outcomes. Work discipline also demonstrated a positive and significant effect, emphasizing that compliance with work rules, standards, and operational procedures supports consistent performance. Simultaneously, work motivation and work discipline were found to significantly influence employee performance. The study concludes that strengthening motivation and enforcing effective work discipline are essential strategies for improving employee performance and maintaining business sustainability in the culinary sector.